Diversity and ethnozoological study of small mammals in villages of the Pendjari Biosphere Reserve in Northern Benin - DJAGOUN, CHABI ADÉYÈMI SYLVESTRE; KINDOMIHOU, M. VALENTIN; SINSIN, Brice (My University, 2009)
Research on conservation of wildlife in reserves in Benin has focused on large mammals due to their appeal for hunting, tourism and related uses. To fill this gap information on small mammals this study aims to assess the diversity and ethnozoology of small mammals at the border of Pendjari Biosphere Reserve (PBR). In this purpose, some semi-structured dialogues and interviews based on questionnaire allow us to establish relationship between small mammal and humans in PBR. Villages were chosen on the basis of socio-cultural group and their proximity and access to resources. Twelve (12) villages of three socio-cultural groups were considered and thirty people (hunters, farmers, and park guards) were surveyed in each village. A total of 43 species of small mammals were inventoried according to local perception. Small mammals constitute an important food resource in the study area except (a) those having nauseous secretions and (b) those which represents a totem for some social clans. Eleven species were listed as priority foods. Small mammals are used for medicinal purposes to treat belly aches, incurable wounds, earaches, sexual impotence and abscess. Some species such as squirrels are threatened because of their negative effect on domestic poultry and on crops such as corn, sorghum and rice. The domestication of some species, the grass-cutter and the hare, are frequently requested as is the creation of locally managed poultry farms which could reduce the dependence of local populations on small mammals thus ensuring their conservation.
Keywords: Small mammals; local knowledge; Pendjari Biosphere Reserve; Benin